Black Soldier Fly (Hermetia illucens): A Proteinous Substitution of Soybean and Fish Meal for Broiler and Layer Chicken: A Review - Md. Amir Hossain; Md. Jamal Uddin Bhuiyan (Poultry Science Journal, 2023)
Protein source feed components are particularly important in broiler and layer feed formulation. Protein-rich insects may be the greatest substitute for protein-rich feed items such as fish and soybean meals. The black soldier fly (BSF) (Hermetia illucens) is an excellent example of an organism that can transform organic waste into protein, lipids, chitin, and other substances. Black Soldier Fly larvae (BSFL) have 42% crude protein, 29% fat, and 23% moisture content on a dry matter (DM) basis. Without specific infrastructure, commercial manufacturing of BSF is achievable. BSF could be used in poultry feed to help reduce pollution. A buildup of organic wastes may result in a possible pollution issue but BSF can transform a wide range of organic waste into a source of protein for poultry. Moreover, the most economical diets were those that had 25% and 100% of Black Soldier Fly Larvae Meal (BSFLM), respectively. The most significant benefit of BSF as a chicken feed ingredient is that it might be a sustainable protein source and a cost-effective replacement for high-cost protein feedstuffs. The importance of the BSF as a potential source of organic protein for broiler and layer chicken production is highlighted in this review of the literature.